A DESCRIPTIVE STUDY OF STUDENTS’ ABILITY IN PRONOUNCING WORD STRESS IN MONOPHTHONGS - Renda Nadi; Sutami Dwi Lestari; Wulan Wangi (Prodi Pendidikan Bahasa Inggris, Universitas PGRI Banyuwangi, 2025)
This research aimed to know the students’ ability in pronouncing monophthong of the X PPLG 1 at SMKN 1 Banyuwangi. The researcher used descriptive quantitative method. This research used test and record to collect the data. The data was obtained by analyzing the students’ ability in pronouncing word stress (primary and secondary stress) in monophtongs. The researcher used twelve (12) monophthongs in this research, namely [i:], [I], [e], [ӕ], [a:], [ɒ], [ɔ:], [ʊ], [u:], [Ʌ], [ɜ:], and [ә]. There were 31 students as the respondent in this research. The data processing method was divided into four stages namely, data collection, data processing, data analysis, and data description. Based on the research findings, the researcher found the word that the results of this research indicated the students’ ability in pronouncing primary stress were 84% and secondary stress were 82%. The classification of the students’ ability in pronouncing both primary and secondary stress were categorized as “very good”.